1994
DOI: 10.1007/bf01310789
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an N-linked glycan in the V1-loop of HIV-1 gp120 influencing neutralization by anti-V3 antibodies and soluble CD4

Abstract: Glycosylation is necessary for HIV-1 gp120 to attain a functional conformation, and individual N-linked glycans of gp120 are important, but not essential, for replication of HIV-1 in cell culture. We have constructed a mutant HIV-1 infectious clone lacking a signal for N-linked glycosylation in the V1-loop of HIV-1 gp120. Lack of an N-linked glycan was verified by a mobility enhancement of mutant gp120 in SDS-gel electrophoresis. The mutated virus showed no differences in either gp120 content per infectious un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
40
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 21 publications
5
40
0
Order By: Relevance
“…Plasmid DNA was isolated (Qiagen) and transfected into the CD4 + cell line H9 using a modified DEAE-dextran method as described elsewhere (Gram et al, 1994). Supernatants were harvested at the peak of antigen production, filtered (0-45 ~tm), divided into aliquots and stored at -8 0 °C until use.…”
Section: Nf-a-920smentioning
confidence: 99%
“…Plasmid DNA was isolated (Qiagen) and transfected into the CD4 + cell line H9 using a modified DEAE-dextran method as described elsewhere (Gram et al, 1994). Supernatants were harvested at the peak of antigen production, filtered (0-45 ~tm), divided into aliquots and stored at -8 0 °C until use.…”
Section: Nf-a-920smentioning
confidence: 99%
“…Just as the acquisition of particular N-linked sites decreases neutralization sensitivity, elimination of N-linked sites at the same or nearby locations has been shown to increase neutralization sensitivity within both HIV-1 and SIV strains, particularly in the V1/V2 and V3 loops (4,16,27,34,45,48,51). Less is known with regard to the effects of mutagenesis of glycosylation sites outside of the V1/V2 and V3 loops on neutralization sensitivity of SIV or HIV.…”
mentioning
confidence: 99%
“…Loss of particular glycans can also affect viral infectivity, possibly through structural alterations that influence the ability of the glycoprotein to bind its receptors, monomer interactions within the trimer, or interactions of the surface and transmembrane fusion proteins (31,42,55). However, many single and multiple glycosylation sites have been shown to be dispensable to viral replication within HIV-1 gp41 (11,23) and gp120 of both HIV-1 (4,16,25,26,34,51) and simian immunodeficiency virus (SIV) (39,47,48). The dispensability of some of these N-linked glycans to viral replication and the greater sensitivity of some mutants missing glycan attachment sites to antibodymediated neutralization (4,16,27,34,36,45,48,51) suggest that these glycans may also serve to shield the spike from recognition by antibodies.…”
mentioning
confidence: 99%
“…Patterns of addition and relocation of N-linked glycosylation sites during the course of HIV and SIV infection suggest an evolving "glycan shield" in response to antibody selection (4,8,26,33,38). Just as the acquisition of particular N-linked sites decreases neutralization sensitivity, the elimination of N-linked sites at the same or nearby locations has been shown to increase neutralization sensitivity for both HIV-1 and SIV (5,9,10,12,13,16,21,31,33). Reitter et al previously demonstrated that a mutation of specific Nlinked glycosylation sites in the V1-V2 region of gp120 of SIVmac239 results in replication-competent viruses capable of eliciting increased levels of antibodies with neutralizing activity against the parental wild-type strain SIVmac239 (32,33).…”
mentioning
confidence: 99%
“…The dispensability of some N-linked glycans for viral replication and the greater sensitivity of some glycan-deficient mutants to antibody-mediated neutralization suggest that these glycans may serve in part as barriers to shield the virus from effective antibody recognition (5,10,12,13,15,16,21,23,31,32,36). Variations in the number and location of glycosylation sites, particularly within the V1/V2 and V3 loops but also on the "silent face" of gp120, often correlate with altered sensitivity to neutralizing antibodies (1,6,11,21,22,34).…”
mentioning
confidence: 99%